KOMBINASI PATI SAGU DAN MODIFIED CASSAVA FLOUR (MOCAF) DALAM PEMBUATAN NUGGET IKAN GABUS - Simanjuntak, Elfrida Agustina; Effendi, Raswen; Rahmayuni, Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study is to find the best mix combination of sago starch and modified cassava flour (mocaf flour) to make fish cork nugget, which meets chemical standards and sensory assessment. The study was conducted by Non-factorial Fully Randomized Design, with five treatments with four repetition. Treatments were indicated by PT1 (sago starch 15, mocaf flour 0), PT2 (sago starch 10, mocaf flour 5), PT3 (sago starch 7.5, mocaf flour 7.5), PT4 (sago starch 5, mocaf flour 10), PT5 (sago starch 0, mocaf flour 15). Changing in water, ash, fat, protein and carbohydrate percentage was observed and sensory assessment (descriptive and hedonic) in food color, aroma, taste and texture was also applied. Data was analyzed by ANOVA and DNMRT with 5% error. The result indicated that the treatments was significance. The best treatment is PT4 (sago starch 5 and mocaf flour 10) that gives 51.86% water, 2.23 % ash, 13.38% fat, 17.29% protein and 15.24% carbohydrate. Keywords: Sago starch, modified cassava flour and fish cork nugget.